2018
DOI: 10.3390/ijms19113488
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Hydrochloride-Loaded PLGA Nanoparticle in Periodontal Disease Experimental Model Using Diabetic Rats

Abstract: Evidence shows that metformin is an antidiabetic drug, which can exert favorable anti-inflammatory effects and decreased bone loss. The development of nanoparticles for metformin might be useful for increased therapeutic efficacy. The aim of this study was to evaluate the effect of metformin hydrochloride-loaded Poly (d,l-Lactide-co-glycolide) (PLGA)/(MET-loaded PLGA) on a ligature-induced periodontitis model in diabetic rats. MET-loaded PLGA were characterized by mean diameter, particle size, polydispensity i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 37 publications
2
57
0
Order By: Relevance
“…The specific delivery of anti-inflammatory agents to the target site could potentially increase their therapeutic concentration in the inflamed tissue with reduced side effects (Gendelman et al, 2015), and the use of PLGA is particularly suitable to this application because of its favorable biodegradability and non-immunogenicity (Lamprecht et al, 2001). Davoudi et al (2018) described a carrier within a carrier system using intestinal organoids to transport 5-ASA encapsulated PLGA nanoparticle to treat inflammatory bowel disease, and Perreira's research involved the development of a metformin loaded nanoformulation that showed efficacy against periodontal inflammation in diabetic rats (Pereira et al, 2018). Gholizadeh et al (2018) have formulated a dactolisib-PLGA nanoparticle that showed activity against inflamed endothelial cells and more recently, Yang (2019) group reported the synthesis of a crocetin-loaded nanoparticles that reduced the level of pro-inflammatory cytokines in renal tissue and therefore shows potential for the treatment of diabetes induced nephropathy.…”
Section: Inflammatory Disordersmentioning
confidence: 99%
“…The specific delivery of anti-inflammatory agents to the target site could potentially increase their therapeutic concentration in the inflamed tissue with reduced side effects (Gendelman et al, 2015), and the use of PLGA is particularly suitable to this application because of its favorable biodegradability and non-immunogenicity (Lamprecht et al, 2001). Davoudi et al (2018) described a carrier within a carrier system using intestinal organoids to transport 5-ASA encapsulated PLGA nanoparticle to treat inflammatory bowel disease, and Perreira's research involved the development of a metformin loaded nanoformulation that showed efficacy against periodontal inflammation in diabetic rats (Pereira et al, 2018). Gholizadeh et al (2018) have formulated a dactolisib-PLGA nanoparticle that showed activity against inflamed endothelial cells and more recently, Yang (2019) group reported the synthesis of a crocetin-loaded nanoparticles that reduced the level of pro-inflammatory cytokines in renal tissue and therefore shows potential for the treatment of diabetes induced nephropathy.…”
Section: Inflammatory Disordersmentioning
confidence: 99%
“…Metformin, the first-line medication for the treatment of type 2 diabetes, is also considered an HMGB1 inhibitor because it directly binds HMGB1 and inhibits the pro-inflammatory activity (63). Metformin and metformin hydrochloride-loaded poly lactic-co-glycolic acid nanoparticles decreased the inflammatory response and bone loss in a rat periodontitis model (64,65). These findings indicate that metformin does not only have a hypoglycemic action but also has an anti-inflammatory effect to block HMGB1, and it might be effective in diabetes-associated periodontitis.…”
Section: Hmgb1 Blockade Inhibits Periodontitis Progressionmentioning
confidence: 99%
“…After full reading, 10 articles were excluded (Supplemental Table S2). Finally, 11 studies were included: 2 with antibacterial agents [26,27], 8 with anti-inflammatory agents [28][29][30][31][32][33][34][35] and 1 with both [36]. The process of article selection is summarized in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…The follow-up of the studies was up to 28 days. Two studies used mice [27,28] and 9 used rats [26,[29][30][31][32][33][34][35][36] (including one with systemically compromised animals with diabetes mellitus [32]). Number of animals ranged between 4 and 20 per group.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%